Physiological and Biochemical Responses of Bisbul (Diospyros discolor Willd.) Seedlings to Varying Artificial Light at Night (ALAN) - Rismona, Nurwani; Hamim, Hamim; Ning Tyas, Kartika; Damayanti, Frisca; Kusumaningtyas Pitaloka, Mutiara; Putri Maulida, Azkia; Triadiati, Triadiati (Bogor Agricultural University, Indonesia, 2026)
Artificial light at night (ALAN) can significantly affect plant physiology, as many physiological processes are light-dependent. However, studies investigating the specific effects of ALAN on plants remain limited. This study aimed to assess the impact of ALAN on the growth and metabolite composition of bisbul (Diospyros discolor Willd.). The experiment was conducted in Nursery 2 of the Bogor Botanical Gardens over 12 months. A split-plot factorial design was employed with three replications, each consisting of three one-year-old seedlings. The main plots were assigned to light color treatments (control, red, green, and blue), subplots to light intensity levels (control, high, and low), and sub-subplots to illumination durations (0, 1, 6, or 12 hours) applied for 0, 2, or 7 nights/week. ALAN treatments were administered continuously for one year. The results indicated that blue light significantly increased leaf senescence, particularly under BH-6(2), BH-12(2), and BH-12(7) treatments. Conversely, high-intensity red light reduced plant height, shoot dry mass, photosynthetic rate, and chlorophyll content. Metabolite profiling revealed decreased levels of secondary metabolites such as caffeic acid and catechin, while compounds such as nicotinamide, L-proline, linolenic acid, and coumarin increased. These findings suggest that prolonged exposure (6-12 hours) to high-intensity red or blue light can disrupt circadian rhythms and impair physiological functions.